Capitalizing Networked Learning: Connectivism, Multiliteracies and the Architectonics of Pedagogy - Dennis, Jeremy (Journal of Contemporary Issues in Education, 2024)
As connectivism is increasingly accepted as a theory of learning for the digital age, scholars and practitioners in education often overlook the dilemma that this creates for its most ardent advocates. In the academic literature, we increasingly find scholarly works that present insouciant descriptions of connectivism. However, such practices often underplay or ignore critiques of connectivism, allowing many of our contentions about its epistemological character and pedagogical effectiveness to calcify. In fact, it is becoming increasingly difficult to rationalize why so many educators have endorsed connectivism as a new theory of learning when there continues to be a need for more empirical testing and greater philosophical substantiation. To illustrate this paradox, this paper examines Stephen Downes’s consideration of connectivism and his connectivist model of literacy. Using the dialogic philosophy of Mikhail Bakhtin, it introduces an architectonic model of connectivism and multiliteracies as an alternative discourse and pedagogical paradigm. A key finding from this study suggests that the lack of attention to capitalist practices, power, and the intermediality of texts in networked learning help to conceal the ways in which connectivist practices rearticulate behaviorism.